Carnosol Maintains Intestinal Barrier Function and Mucosal Immune Homeostasis in DSS-Induced Colitis - Xu, Xiang; Zhang, Gao; Peng, Kun; Gao, Yanping; Wang, Jinxia; Gao, Caiping; He, Chong; Lu, Fang (Frontiers in Nutrition, 2022)
Backgournd: Ulcerative colitis (UC) is a chronic inflammatory disease, characterized by recurrent flares of mucosal inflammation, which is limited in the colon and rectum. Compromised epithelial barrier functions have been indicated in the initiation of UC. Carnosol (CA), a natural active ortho-diphenol diterpene compound, is one of the active ingredients in plants such as rosemary and sage. The anti-inflammatory and anti-oxidative effects of CA have been reported in several animal models, but its effect on mucosal inflammation remains elusive. Methods: we established a mouse experimental colitis model characterized by epithelial barrier destruction using dextran sulfate sodium (DSS). CA was intraperitoneally administrated. Flow cytometry was performed to determine phenotypes of intraepithelial lymphocytes and lamina propria cells. qRT-PCR was used for gene expression. Results: We found CA significantly alleviated DSS-induced colitis in mice marked by relieved clinical symptoms and colonic pathological damage. Inflammatory cell infiltration and cytokine expression in the colon were suppressed by CA during colitis. Furthermore, CA restored epithelial barrier functions and intestinal intraepithelial lymphocyte (IEL) homeostasis in mice with DSS insults. Mechanistically, we induced endoplasmic reticulum (ER) stress in HCT-116 cells (an intestinal epithelial cell line) with thapsigargin, and CA reversed this effect. In addition, we collected inflamed mucosal biopsies from 23 patients with UC, and cultured overnight with or without CA, showing CA significantly reduced expression of ER stress signaling molecule and pro-inflammatory agents. Conclusion: Our data demonstrate that CA acts as an effective drug for experimental colitis and maintains proper epithelial barrier functions via suppressing epithelial ER stress, providing new evidence that CA might be a promising therapeutic candidate for UC.